(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Pedagogical skills are essential for educators to create an effective learning environment that promotes the development of students’ knowledge and skills. This article explores the importance of pedagogical skills in education, including the methods used by educators to promote student learning. The results show that educators with strong pedagogical skills can positively influence students’ academic performance and overall success in life